An Accelerometer Sensor-Based Digital Twin Framework For Structural Health Monitoring Of Cultural Heritage Buildings: A Case Study Of Jakarta Cathedral - Benedictus Wishnu Wintang Kencana; Budy Purnomo Wasisso; Ayomi Dita Rarasati; Titi Sari Nurul Rachmawati (International Journal of Health Engineering and Technology, 2026)
The maintenance of cultural heritage buildings is gradually shifting from a curative approach toward preventive conservation supported by digital technologies. Although Heritage Building Information Modeling (HBIM) has been widely adopted, the resulting models are generally static and incapable of integrating real-time structural monitoring data. This study employs a qualitative case study approach combined with a literature review. The literature review was conducted to identify variables, subvariables, and indicators, which were subsequently validated by experts. In addition, benchmarking of previous frameworks was carried out to understand existing structures and methodologies. Based on these findings, a framework was developed according to the research requirements and further validated by experts to ensure its reliability and practical applicability. This study proposes a Digital Twin (DT) framework for cultural heritage buildings by integrating geometric building models, historical information, and dynamic data obtained from accelerometer sensors. The framework consists of four main layers: the information source layer, the BIM model layer, the integration layer, and the application layer for visualization and decision-making support. The framework was implemented in the Jakarta Cathedral to evaluate the integration of sensor data into the HBIM environment. Expert validation results indicate that the proposed framework provides a systematic approach to supporting preventive conservation for cultural heritage buildings with complex geometries.